Studi Kinerja Rice Transplanter di Lahan Rawa Pasang Surut di Kalimantan Selatan - Rabiatul Munawarah; Indya Dewi; Zairin Ahmad (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Munawarah R, Dewi I, Zairin A. 2020. Study of rice transplanter performance in tidal swamp land at South Kalimantan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The process of transplanting farming in Indonesia is still dominated by manual methods. Rice transplanter is a machine designed to transplanting in ideal conditions for the sake of faster, easier and more economical utilization. The purpose of testing is to achieve the performance of the rice transplanter machine in tidal swamp land at Batalas Village, Tapin Regency, South Kalimantan. The method used was experimental in the field with several replications. The parameters tested were the number of filled holes, number of perfectly planted seed, fallen seed, floated seed, sinked seed, effective work capacity, theoretical work capacity, work efficiency and field capacity. The results showed that the number of hole was filled up to 93.25% with 98.38% perfectly planted seeds, 1.33% fallen seeds, 0.29% floated seeds and 0% sinked seeds. The effective work capacity and theoretical work capacity of the machine were 0.11 and 0.19 ha/hour respectively so that it. Resulted the work efficiency of 59.01%. The field capacity of the machine to plant one hectare of rice fields was 9.1 hours. The application of rice transplanter in tidal swamp land was potential by increasing the work efficiency and improving water network system.